Beauty, Eating Disorders & Size 0: A Qualitative Enquiry into Fashion's Social Responsibility - Schillebeeckx, Simon J.D. (2007)
The fashion industry has popped up in academic research and the news occasionally regarding counterfeiting (Hilton et al, 2004), labour practices (Anon, 2002; Shaw et al, 2004; Nelson, 2006) and sustainability, which led to the creation of the Ethical Fashion Forum. Following recent attention, this dissertation investigates various discourses on the fashion industry's "corporate social responsibility" in producing an extremely body-conscious and disorderedly eating society. The current thinness-ideal has become an issue tackled by corporate pacesetters and is also addressed by some protagonists within the fashion industry, at least in their rhetoric.